A violência e o feminicídio tem cor : diálogos com o movimento de mulheres negras - Liliane Cristina Martins (2022)
The erasure of the deaths of black women and the various forms of violence we go throughand the confrontations that the organized black women's movement have carried out guided the analysis of this research through black feminism. The annihilation of our subjectivities, by the triple oppression that plagues us daily, racism, sexism and machismo has been worsening verthe years without policies to combat violence against women in Brazil, specifically the Maria da Penha Law. pay attention to intersectionality in politics. We theoretically approach femicide and the various forms of violence against black women, loneliness beyond the affective field, working intersectionally, working intersectionally black women activists cis,trans, heterosexual, lesbian, bisexual. The specific objectives were: to reflect with black women activists on the factors that produce the annihilation of black female bodies today and the waysin which they act; understand how the black women's movement sees the protection network for women in Brazil; understand how they analyze the impacts of the construction of the self- image of black women in Brazil. The methodology chosen was dialogues with seven black women from different regions of Brazil, more specifically Belo Horizonte, Curitiba, Dourados, Recife, Rio de Janeiro and Amapá. The methodology of dialogue bets on the tradition of oralityaspoints of convergence and collective construction, where researcher and enunciators share the experience of being black women activists in Brazil. From the dialogues built with these women, it is possible to point to: the need to discuss the network to combat violence against women with black women within social ovements, as well as demystify the typesof violencesuffered, guiding that much is said about violence physical, but psychological and institutional violence sometimes goes unnoticed; As well as the difference that training within social movements makes a shift in the lives of black women as all the research interlocutors point out, from the youngest to the oldest it is clear how their lives have been transformed when entering movements that dialogue with black feminism and with racial issues, since from then on they built the base to transform the lives of other black women; the importance of self-definition and self-love so that black women can recognize themselves worthy of affection, love and state protection.